AI-DRIVEN ACCOUNTING AND DYNAMIC PRICING STRATEGIES IN THE RESTAURANT INDUSTRY - Ablakulova, Shakhnoza Gayrat kizi; Ganiyev, Ibragim Mamadiyevich (THE INNOVATION ECONOMY, 2026)
As the restaurant sector undergoes digital transformation, this study analyzes the efficiency of AI-powered systems in managing finances and optimizing prices. Through an examination of automated inventory control and adaptive pricing algorithms, the article demonstrates how AI reduces human error and responds to market fluctuations. The findings suggest that AI is no longer optional but a critical tool for enhancing restaurant ROI, streamlining operations, and maintaining a leading edge over competitors.